Early stage Acute B lymphocytic leukemia presenting with symptoms of ankylosing spondylitis (AS): A case report. Issue 15 (April 2020) - Liu, Wei; Chen, Guangfeng; Xu, Bing; Sun, Suping; Tian, Jingzhen; Zhang, Yingying
Abstract: Rationale: Acute lymphoblastic leukemia (ALL) has acute and severe onset characterized by fever, moderate to severe anemia, bone and joint pain, and sternal tenderness. It is easy to be misdiagnosed as rheumatic disease when joint pain is the first symptom. Patient concerns: A male Han, 18 years of age was admitted on July 15th, 2016 for multi-joint swelling and pain with intermittent fever for half a year which had aggravated in the last 10 days. Diagnosis: Based on symptoms, imaging, family history, and blood tests, he was first diagnosed with ankylosing spondylitis, but he was refractory to treatment. Bone marrow biopsy then revealed acute B-lymphoblastic leukemia (possibility Pro-B-ALL). Interventions: The patient was transferred to the hematology department on July 23rd, 2016 for chemotherapy. Outcomes: No joint pain occurred during follow-up, which ended on November 4th, 2018. Lessons: ALL may present with symptoms suggestive of rheumatic diseases like ankylosing spondylitis. Physicians should be aware of this possibility, especially in young patients.